Drainage Troughs as a Protective Measure in Subway–Pedestrian Collisions: A Multibody Model Evaluation - Daniel Hall; Kevin Gildea; Ciaran Simms (Applied Sciences)
Introduction: Subway–pedestrian collisions are a significant and growing problem, but they are poorly understood. This study presents the first subway–pedestrian collision model with the aim of evaluating the baseline safety performance of an R160 NYC train and track combination and the potential safety effects of drainage trough depth. Methods: A baseline simulation test sample of 384 unique impacts (8 velocities (2–16 m/s), 24 positions (standing jumping and lying), and 2 track types (flat and crossties)) was created in MADYMO. The full simulation test sample (N = 1920) included with various depth drainage troughs (0–1 m). Head injuries and wheel and third rail contacts were evaluated. Results: Limb–wheel contact occurred in 60% of scenarios. Primary and secondary contact HIC15 showed similar high severity, with an HIC15 < 2000 (88% risk of AIS 4+) in 29% of results for both train and ground contact. Impact velocity strongly influences primary contact HIC15 with limited effect on secondary contact. Impact velocities between 6 and 16 m/s showed little change in wheel contact. Increasing the trough depth up to 0.5 m showed a decrease in wheel contact probability with little increase in secondary contact. No further benefits were found above 0.5 m. Conclusions: A subway–pedestrian collision model is presented which predicts that wheel–pedestrian contact risk can be reduced with a 0.5 m drainage trough. The model suggests that slower impact velocities may reduce head injury risk for primary contact; however, this will have less effect on injuries caused by secondary and wheel contact.